PHARMACEUTICAL CARE IN SMOKING CESSATION FOR ELDERLY PATIENTS (REMUNOM, 2025)
Nicotine, the main psychoactive substance present in tobacco, acts directly on the central nervous system, being the main cause of chemical dependence associated with smoking. Among the elderly, its effects become more intense due to the physiological vulnerabilities of aging. Furthermore, cultural and social factors that have normalized smoking throughout life reinforce the need for empathetic, educational, and integrated therapeutic approaches. In this context, the pharmacist assumes a strategic role in promoting smoking cessation, contributing to clinical guidance, treatment adherence, and the application of protocols aimed at reducing nicotine dependence. This study aimed to analyze the ways in which pharmacists act in smoking cessation among the elderly. To this end, an integrative literature review was conducted in the SciELO, PubMed, and Lilacs databases, using the descriptors "Smoking," "Smoking cessation," "Elderly," "Pharmaceutical care," "Pharmaceutical intervention," and "Health education," combined with the Boolean operator "AND." Articles published between 2018 and 2025, peer-reviewed and available in full, were included. The results demonstrated that pharmaceutical interventions play a fundamental role in the success of smoking cessation programs in the elderly, strengthening the therapeutic bond, promoting greater adherence to treatment, and reducing relapse rates. It is concluded that the pharmacist's role represents an important instrument for promoting health and addressing smoking in the elderly population, contributing to healthy aging and strengthening public policies for tobacco control.